HUMAN RESOURCE DEVELOPMENT PRACTICES IN SOME SELECTED BUSINESS ENTERPRISES IN BANGLADESH: AN EXPLANATORY STUDY - Mohammad Aktaruzzaman Khan; Saleh Jahur (Universitas Trisakti, 2007)
Rapid changes in technology and global structure have made business and finance environment most competitive across the world. To cope with these changes, business firms have urgently required the development of their human resources as one of the most human resources strategies. A well-motivated skilled work force is crucial if an economic unit is to complete effectively both in the national as well as global markets. The present study has examined the FIRD practices of 38 business firms of different economical important industries. It has found that HRD practices with respect to the training methodology, training areas, techniques of importing training etc. across the sample enterprises differ substantially. It has suggested some important policy measures such as linking training to 'strategic coal', delivery of programs using sophisticated methodology. policy for selecting trainers. etc. in order to make the training program goal oriented and consistent.JEL Classification:Key words: Human Resource Development, Training. Employees, Trainer. Performance of Training. and Training Programs.